Fuzzy Topsis untuk Meningkatkan Akurasi dan Objektivitas Bobot pada Seleksi Vendor PT. Telkomsel TTC BSD - Abi Tulkhah; Aries Saifudin (Jurnal Informatika Universitas Pamulang, 2019)
Selection of vendors in PT. Telkomsel TTC (Telkomsel Telecommunication Center) BSD has some shortcomings that their maintenance costs in excess of the targeted system, and the processing time exceeds the specified time limit. The TOPSIS method can be applied to solve the problem by selecting the alternatives which have the shortest euclidian distance from the positive ideal solution. Ranking and weighting of criteria useful for determining solutions in the TOPSIS method. However, in many circumstances, sometimes the data obtained is inadequate and causes it cannot predict preference values correctly. Fuzzy logic can be used to help determine preference values in a structured manner. Fuzzy theory can be used to measure the concept of uncertainty more objectively than humans. In this study, the application of fuzzy TOPSIS method used to select the best vendors in PT. Telkomsel TTC BSD. The results of the research are the TOPSIS method is better than Fuzzy TOPSIS method.